Evaluation of mini-VIDAS rapid test for detection of Listeria monocytogenes from production lines of fresh to cold-smoked fish - Vaz-Velho, Manuela (2011)
This study was conducted to evaluate the efficacy of the mini-VIDAS Listeria monocytogenes (LMO) system (BioMe´rieux Vitek, Inc., Missouri, USA) for detection of L. monocytogenes in environmental and fish samples from three Portuguese cold-smoking plants and from their fresh fish suppliers. Mini-VIDAS-LMO is a fully automated system that uses fluorescent ELFA (Enzyme Linked Fluorescent Assay) technology for detection of Listeria monocytogenes antigens in food. It can be a rapid screening method alternative to time consuming classical isolation and identification. Two hundred and ninety five samples were tested in mini-VIDAS-LMO and in parallel by the ISO 11290-1 traditional protocol. The mini-VIDAS-LMO detected 8 of the 11 confirmed positive samples and presented 11 false positive results. The specificity of the mini-VIDASLMO found in this experiment was 0.96 and the sensitivity 0.73